2020
DOI: 10.1111/1365-2745.13482
|View full text |Cite
|
Sign up to set email alerts
|

Post‐disturbance conifer tree‐ring δ15N reflects openness of the nitrogen cycle across temperate coastal rainforests

Abstract: Post‐disturbance losses in nitrogen (N) may diminish forest productivity, and soils with inherently ‘open’ N cycles are considered the most vulnerable to leaching losses of NO3‐. Monitoring ongoing N depletion from soil profiles is challenging, but tree‐ring δ15N of regenerating stands may offer an effective method for assessing site‐specific, long‐term soil N dynamics. Evidence to date is mixed, however, and includes increasing, unchanging or decreasing tree‐ring δ15N in young stands following stand‐level dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…High rates of N mineralization are typical for fertile (low C : N) soils of perhumid rainforests (Kranabetter et al ., 2021), and consequently, the enhanced concentration of sporocarp N observed in the endemic group can likely be attributed to effective exploitation of NH 4 + . This may be achieved by differential expression and regulation of membrane proteins (Casieri et al ., 2013), a reduction in futile cycling and NH 4 + efflux from roots (Hawkins & Robbins, 2022), and unique storage and transfer mechanisms, such as intracellular vesicle packaging and diffusion, that permit high N status without toxicity (Chalot et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High rates of N mineralization are typical for fertile (low C : N) soils of perhumid rainforests (Kranabetter et al ., 2021), and consequently, the enhanced concentration of sporocarp N observed in the endemic group can likely be attributed to effective exploitation of NH 4 + . This may be achieved by differential expression and regulation of membrane proteins (Casieri et al ., 2013), a reduction in futile cycling and NH 4 + efflux from roots (Hawkins & Robbins, 2022), and unique storage and transfer mechanisms, such as intracellular vesicle packaging and diffusion, that permit high N status without toxicity (Chalot et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…High rates of N mineralization are typical for fertile (low C : N) soils of perhumid rainforests (Kranabetter et al, 2021), and consequently, the enhanced concentration of sporocarp N observed in the endemic group can likely be attributed to effective exploitation of NH 4 + . This may be achieved by differential expression and regulation of membrane proteins (Casieri et al, 2013), a reduction in futile cycling and NH 4…”
Section: Nutritional Attributes Of Endemic Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Plants with higher NRE generally produce lower quality litter, which could slow down litter decomposition, N mineralization rates and the following soil N cycling processes (Aerts, 1997; Vitousek, 1982), resulting in less N losses from the ecosystem. Ecosystems with low‐fertility soils have been found to have more closed N cycle, which reinforces the competition between plants and microbes for N (Kranabetter et al, 2020). On the contrary, ecosystems with high‐fertility soils may have more open N cycle with relatively high nitrification and denitrification rates and relatively large fluxes of N leaching and N gaseous losses (Högberg et al, 2017; Schimel & Bennett, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of N resorption fluxes not only influences plant nutrients (Zhang et al, 2020), but also affects N losses from the ecosystem (Kranabetter et al, 2020), and then the eco-environmental problems caused by excessive N leaching or emission of reactive N gases. The openness of N cycling is defined as the relative importance of internal N cycling compared to the fluxes of N inputs and outputs (Austin & Vitousek, 1998).…”
mentioning
confidence: 99%